High-performance and functional PBT/EVMG/CNTs nanocomposites from recycled sources by in situ multistep reaction-induced interfacial control. (12th April 2020) - Cao, Ying; Xu, Pengwu; Wu, Baogou; Hoch, Martin; Lemstra, Pieter Jan; Yang, Weijun; Dong, Weifu; Du, Mingliang; Liu, Tianxi; Ma, Piming
Abstract: Super-tough and antistatic poly (butylene terephthalate) (PBT) composites from recycled sources with carbon nanotubes were prepared by a multistep reactive compounding process. The PBT-modification was accomplished using epoxidized elastomers (EVMG), epoxidized multi-walled carbon nanotubes (e-CNTs) and epoxidized rheology modifiers (ADR). The reaction between epoxy and PBT-COOH (or –OH) groups enhanced the interfacial bonding between the PBT matrix and the dispersed EVMG and CNTs phases. Moreover, the distribution of CNTs is exclusively in the PBT phase. The presence of ADR resulted in a larger viscosity ratio of the PBT phase to the EVMG phase due to the PBT chain extension and branching, which led to a smaller EVMG particle size and a shorter inter-particle distance. Consequently, both the mechanical properties and the electrical conductivity of the PBT composites were considerably improved due to a synergistic effect of the EVMG and the ADR, e.g., the notched impact strength of the PBT composites reached up to 88 kJ/m 2 and the percolation threshold value for conductive network was reduced by 27%. The super-tough and antistatic PBT composites designed in this study may broaden the application range of PBT in automotive and electrical applications. Graphical abstract: Image 1